Assessing the effectiveness of The Extraordinary Territorial Public Health Commissions coordination mechanisms in the COVID-19 response in Republic of Moldova: coordination and capacity gaps - Demiscan, Daniela (One Health & Risk Management, 2025)
Introduction. The COVID-19 pandemic highlighted the need for effective coordination in managing health crises. In the Republic of Moldova, the response was managed by the National Extraordinary Public Health Commissions but implemented by the Extraordinary Territorial Public Health Commissions (TEPHCs). Materials and methods. The observational epidemiological study employed a cross-sectional design, collecting data through an online questionnaire between December 2021 and March 2022 from 294 members (94.8% response rate) of TEPHCs from 35 territorial units. The sample included 179 women (60.9%) and 115 men (39.1%). The study assessed coordination mechanisms, existing legislation, and implementation barriers. Results. The results show a high level of awareness of the National Response Plan to COVID-19 (92%) and recognition of its importance (95%). However, only 26% felt that the measures were clear and easy to implement. Resource issues were significant, with 65% reporting staff shortages and 75% reporting financial constraints. Despite 67% of respondents having received training, 94% expressed a need for further support in pandemic management. Conclusions. TEPHCs have been essential in managing the pandemic at local level, but their effectiveness has been hampered by an inadequate legal framework, poor communication and lack of adequate resources and training. The study recommends updating the legal framework and improving coordination mechanisms. Additional investments in preparedness are vital.